The experience of therapy by therapists and survivors after exposure to armed robbery - SJ Marais (AOSIS, 2003)
In this article the results of research undertaken to explore the experience of therapy by respectively the survivor of armed robbery and the therapist of the survivor of armed robbery in the case where therapy is prematurely terminated by the survivor of armed robbery are discussed. A high percentage of therapy for the survivor of armed robbery is being terminated prematurely by the survivor. This might be the reason for failing to use all possible opportunities to recover within reasonable time. The research questions that arouse are: "How do survivors of armed robbery experience therapy after being exposed to armed robbery?" and "How do therapists experience therapy for the survivor of armed robbery?" A qualitative, exploratory, descriptive and contextual research design was utilised. Phenomenological, semi-structured interviews were conducted with survivors of armed robbery and therapists of survivors of armed robbery to explore and describe their experiences.